Mg-Doped PLA Composite as a Potential Material for Tissue Engineering—Synthesis, Characterization, and Additive Manufacturing - Fawad Ali (2154529) (2023)
Magnesium (Mg)/Polylactic acid (PLA) composites are promising materials for bone regeneration and tissue engineering applications. PLA is a biodegradable and biocompatible polymer that can be easily processed into various shapes and structures, such as scaffolds, films, and fibers, but has low biodegradability. Mg is a biocompatible metal that has been proven to have good biodegradability and osteoconductivity, which makes it suitable for bone tissue engineering. In this study, we prepared and characterized a Mg/PLA composite as a potential material for direct ink writing (DIW) in 3D printing. The results showed that the addition of Mg has a significant impact on PLA’s thermal and structural properties and has also significantly increased the degradation of PLA. XRD was used to determine the degree of crystallinity in the PLA/Mg composite, which provides insight into its thermal stability and degradation behavior. The crystallization temperature of PLA increased from 168 to 172 °C for a 15 wt% Mg incorporation, and the melting temperature reduced from 333 °C to 285 °C. The surface morphology and composition of these films were analyzed with SEM. The films with 5 wt% of Mg particles displayed the best-ordered honeycomb structure in their film form. Such structures are considered to affect the mechanical, biological and heat/mass transfer properties of the Mg/PLA composites and products. Finally, the composite ink was used as a feed for direct ink writing in 3D printing, and the preliminary 3D printing experiments were successful in resulting in dimensionally and structurally integral scaffold samples. The shape fidelity was not very good, and some research is needed to improve the rheological properties of the ink for DIW 3D printing. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma16196506